Physical inactivity and anthropometric measures in schoolchildren from Paranavaí, Paraná, Brazil - Flávio Ricardo Guilherme; Carlos Alexandre Molena-Fernandes; Vânia Renata Guilherme; Maria Teresa Martins Fávero; Eliane Josefa Barbosa dos Reis; Wilson Rinaldi (Sociedade de Pediatria de São Paulo, 2015)
OBJECTIVE: To investigate the association between physical inactivity and anthropometric measures in schoolchildren from Paranavaí-Parana, Brazil. METHODS: Cross-sectional survey, carried out in July and August 2013. Sample of 566 students (287 boys and 279 girls) from 6th to 9th grade, aged 10 to 14 years, from public and private schools of Paranavaí - PR, Southern Brazil. The variables analyzed were: time of weekly physical activity through a questionnaire (physical inactivity <300 minutes/week), body mass index (BMI) and waist circumference (WC). In the statistical analysis, the U Mann-Whitney and Student's t tests were used for comparison between genders. To identify factors associated with insufficient levels of physical activity, univariate and multivariate logistic regression analysis was applied and expressed in Odds ratio (OR) and 95% confidence interval (95%CI). RESULTS: There was an association between physical inactivity and anthropometric measurements for BMI (p<0.001) and WC (p<0.001), with a prevalence rate of 56.1% and 52.7% of inactive adolescents, respectively. In the multivariate analysis, there was significant association of physical inactivity and overweight (OR 1.8, 95%CI: 1.1-3.0) and with increased waist circumference (OR 2.8, 95%CI: 1.4-3.8). CONCLUSIONS: Inadequate levels of physical activity is a determining factor for overweight and abdominal adiposity. Accordingly, preventive measures should be taken, especially in schools, emphasizing the importance of exercise for body composition control and weight reduction.